Vanguard: Black Veterans and Civil Rights After World War I - Ang, Desmond; Chinoy, Sahil (Quarterly Journal of Economics, 2026)
Nearly 400,000 Black men were drafted into the National Army during World War I, where they toiled primarily as menial laborers in segregated units. Leveraging novel variation from the World War I draft lottery and millions of digitized military and NAACP records, we document the pioneering role these men played in the early civil rights movement. Relative to observably similar individuals from the same draft board, Black men randomly inducted into the Army were significantly more likely to join the nascent NAACP and become prominent community leaders in the New Negro era. We find little evidence that these effects are explained by migration or improved socioeconomic status. Rather, corroborating historical accounts about the catalyzing influence of institutional racism in the military, we show that increased civic activism was driven by soldiers who experienced the most discriminatory treatment while serving their country.